Development of Islamic Higher Education in the Globalization Era: A Study of Global Thinking by Qodry A. Azizy - Huda, Miftahul; Syukur, Fatah; Junaedi, Mahfud (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
Globalization has resulted in rapid changes in various fields and brought many impacts, especially on Islamic education. This study aims to determine the globalization of Islamic education thought of Qodri Azizy, which comes from the question, ‘How is Qodri Azizy’s transformative and futuristic thought? This research has an urgency and uniqueness because Qodri Azizy is an academic in law as his scientific discipline, but his contributions are very interdisciplinary and even greatly influence his contribution to Islamic higher education. This is the embryo of the birth of the Unity of Sciences paradigm at UIN Walisongo. The intellectual biography research used library research with text analysis using a related text analysis approach. The research found: (1) transformative Islamic education ideas of Qodri Azizy (a) religious education and freedom of thought, (b) building and teaching environmental ethics, (c) good deeds and generosity, and (d) creating a culture of useful and productive friendship; (2) the role of Islamic education in globalization era according to Qodri Azizy (a) designing a pattern of development of IAIN Walisongo by opening general scientific discipline with a foundation of Islamic knowledge, (b) studying Islam with social sciences approach, (c) change school management with community-based education, and (d) change education management in IAIN Walisongo toward modern management with an Islamic basis. To the public in general, it is hoped that they will be able to take advantage of Qodri Azizy’s Islamic education ideas as part of the capital to equip the next generation who are Islamic and able to face the changing era.